The Relationship between the Role of the Team Leader and the Performance of the Implementing Nurse in Documenting Nursing Care at Dr. H. Yulidin Away Regional Hospital, Tapaktuan - Anggi Maulida Sari; Samsidar Samsidar; Zakiyah Zakiyah (Program Studi Pendidikan Biologi, 2025)
The team leader is the most important person in organizing, supervising, and ensuring that all team members perform their duties properly. The success of documentation implementation is influenced by the role of the team leader, who acts as a director, motivator, and assessor of the quality of the work of implementing nurses. This article aims to determine the relationship between the role of the team leader and the performance of implementing nurses in documenting nursing care at RSUD dr.H.Yuliddin Away Tapaktuan. The type of research used is an analytical survey. The population in this study were all D3 and S1 nurses. The sampling technique used was accidental sampling with a sample size of 69 people. The results of the cross-tabulation study were obtained from 69 nurses.50 respondents (72.5%) had a good team leader role, and 51 respondents (73.9%) had good nurse performance. The correlation results showed a p-value of 0.013, where α=0.05. Thus, the results of this study indicate a relationship between the two.The role of the team leader in the performance of implementing nurses in documenting nursing care at RSUD dr.H.Yuliddin Away Tapaktuan.